ANALISIS PREFERENSI KONSUMEN TERHADAP PEMBELIAN MINUMAN KOPI DI STARBUCKS SUNCITY MALL SIDOARJO - Aristawati, Diyah Ayu; Hendrarini, Hamidah; Tondang, Ika Sari (Universitas Wahid Hasyim, 2024)
The current competition of the coffee industry makes product attributes and preferences a very important part to be noticed by entrepreneurs as it can be easier to provide what is consumer needs. The study aims to identify consumer characteristics, analyze attributes and levels of interest that are consumer preferences in the purchase of coffee drinks at Starbucks Suncity Mall Sidoarjo. The methods chosen for sampling were accidental samplings, with a total of 100 respondents. In this study, descriptive analysis is used to identify consumer characteristics, while conjoint analysis is applied to differentiate product attributes and the degree of importance to Starbucks coffee drink purchases. Research results showed that most buyers were women aged 17 to 27 with a final background of high school education or equivalent, a job as a student or university student, and have a monthly income of less than Rp 1,000,000. From the preference side, the attributes most attracting consumer attention are the sweet taste of coffee, the price of less than Rp 55,000, promo buy one get one on a particular event, a variety of coffee drinks, getting free items in a condiment bar, the design of a comfortable and attractive place, and easy packaging. Whereas the level of importance of attributes is taste, price, discount, elegance, facilities, packaging, and service.